Exponential stability of a program manifold of indirect control systems - Zhumatov, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish sufficient conditions for the exponential stability of a program manifold of indirect control systems and conditions for the fast operation of a regulator, overcontrol, and monotone damping of a transient process in the neighborhood of the program manifold.